Determinants of Delay in Diagnosis and Treatment in Multi Drug-Resistant Tuberculosis Patients in Health Facilities - Sutanto, Yusup Subagio; Murti, Paulus Wisnu Kuncoro; Reviono, Reviono; Probandari, Ari Natalia; Kurniawan, Hendra (Indonesian Journal of Medicine, 2021)
Background: Multidrug-resistant tuberculosis (MDR-TB) is a serious threat to global TB control programs. According to WHO, there are 23,000 cases of TB multidrug-/rifampicin-resistant (MDR/RR-TB) in Indonesia. In 2017, there were 442,000 of TB cases. There were 8,600 - 15,000 MDR/RR-TB cases, of which 2.4% were new cases and 13% were previously treated TB cases. This study aims to determine the factors that influence the delay in diagnosis and treatment of MDR-TB patients.Subjects and Method: This study was a cross-sectional study conducted at Dr. Moewardi hospital, from September to October 2017, Surakarta, Central Java. A sample of 73 MDR-TB patients with disabilities on medical records was selected for this study. The dependent variables were delay in diagnosis and delay in therapy of MDR-TB cases. The independent variables were age, gender, distance to health facilities, and type of health facilities. Data were collected from medical records of MDR-TB patients who were treated from March 2012 to March 2017. Data were analyzed using the chi-square model.Results: Median delay in diagnosis = 4 days. Median treatment delay = 12 days. The average patient who had delayed MDR-TB therapy (≥4 days) was 44 years old (Mean= 44.19; SD= 12.64). Delay in MDR-TB diagnosis was not significantly associated with gender (OR= 0.53; 95% CI= 0.18 to 1.57; p= 0.264), distance to health facility (OR= 1.56; 95% CI= 0.58 to 4.21; p= 0.389), and type of health facility (OR= 0.60; 95% CI= 0.26 to 1.41; p= 0.983). The average of patient who had delayed MDR-TB therapy (≥12 days) was 41 years old (Mean= 41.39; SD= 12.69). Treatment delay was not significantly related to gender (OR= 0.45; 95% CI= 0.16 to 1.26; p= 0.137), distance to health facility (OR=1.44; 95% CI= 0.55 to 3.78; p= 0.466), and type of health facility (OR= 2.31; 95% CI= 1.03 to 5.21; p= 2.967).Conclusion: There was no statistically significant relationship between gender, distance from the patient's home to health facilities, and type of health facility with the delay in diagnosis and treatment of MDR-TB patients.Keywords: diagnosis, treatment, TB-MDRCorrespondence: Yusup Subagio Sutanto. Department of Pulmonology and Respiratory Medicine, Faculty of Medicine Universitas Sebelas Maret/ Dr. Moewardi Hospital, Surakarta. Jl. Kolonel Sutarto No.132, Jebres, Surakarta, Central Java 57126. Email: dr_yusupsubagio@yahoo.com. Mobile: 0811284165.Indonesian Journal of Medicine (2021), 06(01): 14-22https://doi.org/10.26911/theijmed.2021.06.01.02